Home injuries among children < 6 year old in Taman Soga, Batu Pahat, Johor Darul Takzim, 1994 - Siti Zaleha Mohd Salleh,; Hanafiah Mohd Salleh, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional descriptive study of domestic accidents was conducted in Taman Soga Batu Pahat, Johor Darul Takzim from December l0th. 1993 to January 9th 1994. The aims of this study were to investigate domestic accidents among children with regard to prevalence and factors related to childhood injuries in the home. Data were collected through presurvey and survey via an interview by using pretested questionaires during house visits. Three hundreds and eighty children from 250 mothers were involved in this project. The prevalence rate of domestic accidents among children 3 months to 6 years old was 24.7%. Toddlers had a highest prevalence rate of domestic accidents compared to infant and preschools. The most common place of accidents was within the house (84.1 %)where more than half of the accident occured in the living room. The commonest type of accidents was physical injury. Falls were the leading cause (80.9 %), other children sustained laceration and cut (12.8 %), scalded (4.8 %) and swallowed an object (2.1 %). Most lesions were benign. The most common localization of lesion was head (55.8 %), and lower extrimities (32.5 %). Household furnitures and contructional features of the house cause most accidents. There were statitiscally signifant difference between domestic accidents and etnic groups (p<0.05), level of maternal education (p<0.05), type of houses (p<0.05), numbers of children age 3 months to 6 years in the family and mean age of the children (p<0.05). The factors which related to domestic accidents lead to the conclusion that the main aspects of prevention should be by the creation of a safety environment and parent's education should be improved with emphasis on knowledge of children's normal psychological and motor development and abilities.